Viral warfare: unleashing engineered oncolytic viruses to outsmart cancer’s defenses - Omolekan, Tolulope O.; Folahan, Joy T.; Tesfay, Mulu Z.; Mohan, Harikrishnan; Dutta, Ojasvi; Rahimian, Leila; Ferdous, Khandoker Usran; Ghavimi, Reza; Cios, Aleksandra; Beng, Timothy K.; Francis, Joseph; D'Auvergne, Oswald; et al. (Frontiers in Immunology, 2025)
Oncolytic virotherapy (OVT) has emerged as a promising and innovative cancer treatment strategy that harnesses engineered viruses to selectively infect, replicate within, and destroys malignant cells while sparing healthy tissues. Beyond direct oncolysis, oncolytic viruses (OVs) exploit tumor-specific metabolic, antiviral, and immunological vulnerabilities to reshape the tumor microenvironment (TME) and initiate systemic antitumor immunity. Despite promising results from preclinical and clinical studies, several barriers, including inefficient intratumoral virus delivery, immune clearance, and tumor heterogeneity, continue to limit the therapeutic advantages of OVT as a standalone modality and hindered its clinical success. Recent advances in OV engineering have enhanced viral tropism, immune evasion, and transgene delivery, enabling better tumor targeting and penetration and sustained immune activation in malignant tumors. Moreover, rational combination strategies with immune checkpoint inhibitors (ICIs), chemotherapeutics, and immunometabolic modulators are reshaping OVT into a versatile strategy for precision oncology. This review highlights the mechanistic innovations driving next-generation OV engineering, explores emerging combination regimens, and discusses future directions to overcome resistance and maximize clinical efficacy.